Customer Retention : The Key to Business Success - Kaur, Kawaljit (Journal of Commerce and Trade, 2010)
This Paper measures how customer can be retained and what are the various measures to retain existing customers this leads to increase the lifelong value of the company. This paper has given detailed information about strategies of customer retention and how to win customer through integrated approach. In a competitive marketplace where businesses compete for customers, customer satisfaction is seen as a key differentiator and increasingly has become a key element of business strategy.